Caterpillar hump of right hepatic artery: incidence and surgical significance - Devi Jansirani; N Mugunthan; Vijisha Phalgunan; S Shiva deep (Wolters Kluwer Medknow Publications, 2012)
Background and aims: The right hepatic artery occasionally forms a sinuous tortuousity called as caterpillar hump or Moynihan's hump, which occupies the major portion of Calot's triangle. Due to this variation, inadvertent injury to right hepatic artery may occur during surgical procedures. The aim of the study is to find out the incidence of Caterpillar hump of right hepatic artery in cadavers and to correlate with surgical significance. Materials and methods: Sixty cadavers allotted for the purpose of teaching undergraduate students from the period of 2006 to 2011 were used for this study. Branches of coeliac trunk were traced and right hepatic artery was observed for the presence of caterpillar hump. Results: Caterpillar hump was noted in three out of 60 cadavers (5%). Out of three specimens with caterpillar hump, right hepatic artery passed posterior to common hepatic duct in two specimens and anterior to it in one specimen. The presence of dual loops of right hepatic artery was noted in two specimens and single loop was observed in one specimen. Conclusion: The presence of this variant course of right hepatic artery may lead to the formation of short cystic artery. Thereby, right hepatic artery can be mistaken for cystic artery and may be injured during surgical procedures. The knowledge of caterpillar hump of right hepatic artery is essential for the surgeons to avoid the risk of ischemic necrosis of right lobe of liver.